Entrepreneur Political Skill And Negotiation Outcomes Among Tsmes: The Roles Of Entrepreneurial Orientation, Social Capital And Government Coaching Support As Antecedents - Wee, Nur Melissa Binti Mohammad Faisal (2017)
This study was grounded by Resource-Based View and Behavioural Decision Research. Thus a more holistic research was conducted in order to examine the impact of political skill towards negotiation outcomes and the determinants that will affect politically skilled TSMES entrepreneurs. Data were collected from 123 TSMEs from SME Corporation directories and Malaysia SME directories through self-administered questionnaire developed from related literature. The data collected were analysed using partial least squares-structural equation modelling via Smart PLS 3